Fierce and delicate : essays on dance and illness - Nicholson, Renée K. (West Virginia University Press, 2021)
"In Fierce and Delicate, she looks back on the often confused and driven self she had been shaped into and finds beauty in the small roles she performed. When, inevitably, Nicholson moved on from dancing, severed from her first love by illness, she discovered that she retained the lyricism and narrative of ballet itself as she negotiated life with rheumatoid arthritis. An intentionally fractured memoir-in-essays, Fierce and Delicate navigates traditional geographies-South Florida, Northern Michigan, New York City, Milwaukee, West Virginia-and also geographies of the body. It is a book about the world of professional dance and also about living with chronic disease, about being shattered yet realizing the power to assemble oneself again, in a new way"--